FAKTOR-FAKTOR YANG MENJADI DAYA TARIK PERUSAHAAN DALAM PERSEPSI MILLENNIAL PADA PT GARDA SEKURINDO - Andri Setyawan (2022)
This study aims to explore the factors that are the attractiveness of PT Garda Sekurindo by describing them based on the perceptions of millennial generation employees and determining the factors that are most considered important by millennial employees and proving whether the attractiveness that meets the expectations of millennial employees can increase their loyalty. . This research uses a qualitative approach with a phenomenological study. Data collection techniques used in this study were interviews, observation, and documentation. Participants in this study amounted to 11 people consisting of 7 employees and HRD managers of PT Garda Sekurindo and 3 employees from other similar companies. The results showed that, based on the perceptions of employees from the millennial generation, the factors that became the attraction of PT Garda Sekurindo consisted of 7 factors, namely: work environment, salary and benefits, company image, training and development, career path, and location. work. The factor that is considered the most important by millennial employees working at PT Garda Sekurindo is the work environment. as well as the suitability of the attractiveness offered with what millennial employees are looking for and hope to increase employee loyalty.